THE EFFECT OF BOUNCING LETTERS GAME ON THE ABILITY OF THE EIGHTH GRADER STUDENTS ’ IN WRITING NOTICES - Afore Tahir Harefa (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2020)
Writing the notices becomes one necessary activity before composing the announcements form, displaying information, sharing ideas for the other people, and then putting it into written language form. The Population of this research is the eighth-grader students of SMP Negeri 1 Mandrehe Utara. The eighth-grader's syllabus expected the students to be able to convey something in written notices form. Still, in reality, the students cannot carry something appropriately in the written way of notification. The purpose of this research is to find out whether there is a significant effect of using Bouncing Letters Game on the students' ability in writing notices in the eighth grade of SMP Negeri 1 Mandrehe Utara. The researcher applied quasi-experiment design as a research design. The instrument test that used in this research is an essay test. Then, the researcher did the internal and external validity to validate the instrument test. Afterward, the researcher gave the pretest to both experimental and control classes. The mean mark of pretest for the innovative quality was 63.00 adequate classified while in the control class was 53.50 classified less. The data of pretest for the experimental type was X2 count 3.58 ≤ X2 table 7.82, and in control, the course was X2 count 2.39 ≤ X2 table 7.82 so, both of the data in pretest stated normal distribution. The examination result of homogeneity in pretest was ftable 1.86 ≥ Fcount 1.33 means the sample was homogenous. After did a treatment, the researcher gave a posttest to both experimental and control classes. The mean marks of the posttest for the innovative level are 73.33 classified good, while the control class is 63.67 classified as adequate. The result of hypothesis testing (t-test) was tcount 5,110 ≥ ttable 2.002 so, Ha is acceptable, and H0 is unacceptable. It means that there is a significant effect of using Bouncing Letters Game on students' ability in writing notice in the eighth grade of SMP Negeri 1 Mandrehe Utara in 2013/2014.